Effect of Milk Substitution with liquid whey on the quality properties of fatty cake - Baghdad Science Journal (مجلة بغداد للعلوم)
This study exposed to use the liquid whey (which was produced from of soft cheese processed) partially or completely instead of milk in fatty cake, this whey residue is still not used, instead it is thrown in rivers which effect different environment and economic problems. Different concentrations was used (25% , 50% , 75% , and 100%) of whey in baked cake , Volume , height and other different properties ( panel taste ) was studied too . Sensory evaluation results showed that an improved in all the character of the baked cake was happen by the used of 25% and 50% of the whey in comparison with the control treatment, the 75% replacement showed a decrease in appearance , texture and tenderness , while the degrees of color and flavor was the same as the control treatment .the 100% replacement showed a decrease in shape , volume and other characteristics . Also the study showed that the used of 25% and 50% liquid whey, had no change in both volume and height of cake .while it was decreased in both in 75% and 100% . We conclude that the used of liquid whey did not effected the different characteristics of the cake in comparison with the control 100% milk , the used of 25% and 50% of whey improved some of the characteristics , The cake is not affected by the use of 25,50 and 75% whey .